(untitled) (Research, Society and Development, 2020)
This study aims to analyze adherence to self-care activities of people with diabetes seen in primary care in a municipality in Rio Grande do Sul. This is a cross-sectional, descriptive study with a quantitative approach. Data collection was performed using the Diabetes Self-Care Activities Questionnaire. Data analysis revealed that the item taking DM drugs had the highest adherence rate. The item with the lowest adherence to self-care was to perform specific physical exercise. However, there was a greater adherence in the dimensions of foot care and medication, followed by general, specific food and physical activity. And lower adherence in the blood glucose monitoring dimension. It is concluded that there is a need to plan strategies that can increase the rate of adherence of users to self-care, in order to prevent further complications and health problems.